Allowing students to choose speaking topics to motivate the first year non-major students in learning English speaking at University of Labor and Social Affairs = Cho phép sinh viên tự lựa chọn chủ đề nói để gây hứng thú học nói Tiếng Anh cho sinh viên nă - Hoàng, Thị Lan (University of Languages and International Studies, 2017)
43 p. + CD-ROM